Examining Students’ Perspective of Photovoice on Speaking Class: An Interview Study at Tertiary Level - Jannah, Rodhotul; Basya, Dihliza; Sabartono, Ribut (Linguapedia, 2022)
This research is limited to the students’ perspective toward the use of photovoice in the teaching and learning process. The objective of this study is to explore the perspective of students about the use of photovoice on the teaching and learning process in speaking class. The research use qualitative interview study with a descriptive design. The researchers collected the data by individual semi-structured interviews. The writter choose telephone inteview with current conditions (Covid 19). Data analysis used is thematic analysis by (Braun, Virginia & Clarke, 2006). Interview were transcribed verbatim to ensure data integrity by double-checking the transcripts with recorded interviews.The researh findings show 7 theme based on interview with students who describe their perspectives and experiences in learning photovoice. These themes are: 1) experiences, 2) social, 3) intellectual, 4) speaking, 5) emotion, 6) challanges and difficulties, and 7) future direction of photovoice